Stand for dynamic tests of technical products in the mode of amplitude-frequency modulation with hydrostatic vibratory drive; Journal of Vibroengineering; Vol. 18, iss. 6 - Nizhegorodov A. I. Anatoliy Ivanovich; Gavrilin A. N. Aleksei Nikolaevich; Moyzes [Moises] B. B. Boris Borisovich; Ditenberg I. A. Ivan Aleksandrovich; Zharkevich O. Olga; Zhetesova G. S. Gulnara Santaevna; Muravjev O. P. Oleg Pavlovich; Bets M. Mikhail (2016, 2016)
Title screen